To reflect in the line y = -x + 6, we translate everything down 6 first. This will make it seem like we are reflecting in the line y = -x (x,y) → (x, y-6) Then, to reflect in the line y = -x, we switch the x- and y-coordinates and then make them negative (x,y) → (-(y-6), -x) Then we move everything back up again (x,y) → (-(y-6), -x + 6) I will present to you an example. Reflect the point (-4, 8) in the line y = -x + 6. (-4,8) → (-(8-6), -(-4) + 6) → (-2, 10) You should graph this out to confirm with the reflection line.
Since it must be an integer, 5 would make it up to the full length of the longest line. What you get is not quite a triangle. The way to get a triangle is to add one more to the 5 to make 6